Faktor Determinan Penolakan Imunisasi di Desa Bonjor Kabupaten Temanggung Tahun 2018 - Faridatun Khasanah; Retna Siwi Padmawati (Fakultas Kedokteran Universitas Gadjah Mada, 2019)
Determinant factors immunization refusal in Bonjor Village Temanggung DistrictPurpose: Temanggung district is one of two districts in Central Java that have refusal immunization. Highest refusal immunization in Temanggung district located in Bonjor Village. Based on this, researchers wanted to see determinants of refusal immunization in Bonjor Village. Method: Study design was sequential explanatory mixed method used 1: 1 paired case-control study, which was equipped with qualitative sequential explanatory. Research sample were parents who refused and did not refuse their children to be immunized who lived in Bonjor Village. Quantitative analysis using bivariate analysis and multivariate analysis, while qualitative analysis using data triangulation.Results: Sample collected was 114 heads of families. The results of study showed that 58% respondents had education level of junior high school, 57% working as farmers and the average age of 31.75 years with youngest age was 19 years and oldest was 48 years. The results of multivariate analysis showed that mother's belief in breastfeeding (OR=5.54; 95% CI=1.91-16.05), vaccine was not an option in increasing immunity (OR=20.32; 95% CI=3, 98-103.68), and the experience of mothers that after immunization her child became fussy (OR = 3.92; 95% CI=1.32-1156) had a relationship with the refusal immunization in Bonjor Village, Temanggung District in 2018. Belief and experience of mothers about immunization supporting occurrence of vaccines is not an option in increasing immunity.Conclusion: Increasing knowledge and restoring public belief are initial choices for increasing immunization coverage. Refusal immunization problem cannot be solved by one sector but requires cross-sector cooperation.